Inverse spatially‐offset Raman spectroscopy using optical fibers: An axicon lens‐free approach. Issue 11 (17th July 2019) - Khan, Khan Mohd.; Dutta, Surjendu B.; Kumar, Nitin; Dalal, Anita; Srivastava, Amrita; Krishna, Hemant; Majumder, Shovan K.
Abstract: Inverse spatially offset Raman spectroscopy (I‐SORS) seeks to interrogate deep inside a Raman‐active, layered, diffusely scattering sample. It makes a collimated laser beam incident onto the sample surface in the form of concentric illumination rings (of varying radii) from whose center the back‐scattered Raman signal is collected for detection. Since formation of illumination rings of different sizes requires an axicon to be moved along the axis of the collimated laser beam and axicons below a certain minimum size (~1 inch) are not readily available, this classical configuration incorporating an axicon cannot be used for designing a compact I‐SORS probe of narrower diameter. We report a novel scheme of implementing I‐SORS which overcomes this limitation by implementing ring illumination and point collection using two multi‐mode optical fibers. An important advantage of the proposed scheme is that unlike the previously reported inverse SORS configurations, it does not require physical movement of any of the optical components for generating spatial offsets needed for probing sub‐surface depths. Another advantage is its fiber‐optic configuration which is ideally suited for designing a compact and pencil‐sized I‐SORS probe, often desired in many practical situations for carrying out depth‐sensitive Raman measurements in situ from a layered turbid sample. Abstract : Classical configuration of inverse spatially‐offset Raman spectroscopy (I‐SORS), incorporating an axicon, is not suitable for designing a depth‐sensitive Raman probe of narrower diameter. The paper proposes a novel scheme of implementing I‐SORS using fiber‐optic configuration, which is ideally suited for designing a compact and pencil‐sized I‐SORS probe, often desired in many practical situations for carrying out depth‐sensitive Raman measurements in situ from a layered turbid sample.